Is Person–Organization Fit Beneficial for Employee Creativity? Moderating Roles of Leader–Member and Team–Member Exchange Quality. Issue 3 (8th August 2019) - Seong, Jee Young; Choi, Jin Nam
ABSTRACT: This study investigates the effect of person–organization (PO) fit on employee creativity. We draw on social exchange theory and identify leader–member exchange (LMX) and team–member exchange (TMX) as moderating contingencies. Our empirical analysis based on 167 employee–supervisor dyads confirms that LMX activates the significance of PO fit toward creativity. In addition, under high LMX, PO fit effect on creativity is positive when TMX is high. Subsequent analyses show that employees with high PO fit exhibit the highest level of creativity when LMX and TMX are high. Findings on the three-way interaction among PO fit, LMX, and TMX toward creativity offer new insights into a phenomenon that is mostly neglected in the literature.